2019
DOI: 10.1111/btp.12698
|View full text |Cite
|
Sign up to set email alerts
|

Spit it out: Monkeys disperse the unorthodox and toxic seeds of Clivia miniata (Amaryllidaceae)

Abstract: Seeds of many Amaryllidaceae are unorthodox (recalcitrant) and toxic, and cannot survive ingestion, yet are packaged in brightly colored fruits suggestive of zoochory. Seed dispersal and germination of the understory amaryllid, Clivia miniata, were investigated in KwaZulu‐Natal, South Africa. Motion‐activated cameras revealed that samango monkeys (Cercopithecus mitis labiatus) are the primary disperser of C. miniata seeds. They eat the mesocarp and, to a lesser extent, the exocarp, and spit the large (13 mm di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
3
12
1
1
Order By: Relevance
“…1; Appendix S4). We observed mainly vervet monkeys feeding on Scadoxus fruits, in contrast to Kiepiel and Johnson (2019) who found that samango monkeys were the main dispersers of seeds of Clivia miniata, another member of the Haemantheae, which has fruits and seeds that are similar to those of Scadoxus . This difference in monkey species may reflect that the two Scadoxus species studied here occur in relatively open forest–grassland mosaic habitats preferred by vervet monkeys, while Clivia miniata occurs in homogeneous forest habitats preferred by samango monkeys.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…1; Appendix S4). We observed mainly vervet monkeys feeding on Scadoxus fruits, in contrast to Kiepiel and Johnson (2019) who found that samango monkeys were the main dispersers of seeds of Clivia miniata, another member of the Haemantheae, which has fruits and seeds that are similar to those of Scadoxus . This difference in monkey species may reflect that the two Scadoxus species studied here occur in relatively open forest–grassland mosaic habitats preferred by vervet monkeys, while Clivia miniata occurs in homogeneous forest habitats preferred by samango monkeys.…”
Section: Discussioncontrasting
confidence: 99%
“…For the tree Strychnos mitis , redtail monkeys would most often move away from the plant before spitting out the seeds, although usually still under the tree crown (Lambert 2001). Kiepiel and Johnson (2019) hypothesized that cheek‐pouching may result in occasional long‐distance dispersal but were not able to estimate the number of seeds dispersed beyond their search perimeter of 11 m and thus may have underestimated the prevalence of long‐distance dispersal. By counting all seeds on plants prior to dispersal in this study, we calculated that for both of our study species, the great majority of seeds were dispersed further than our search perimeter (84% greater than 1 m for S. multiflorus subsp katherinae and 79% greater than 1 m (and 78% greater than 2 m) for S. puniceus ) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such plants usually have mechanical or chemical inhibitors in the fruit, either in the exocarp, pulp or seed coat, to achieve the needed dormancy (Jordano, 2000). Once the fruit is consumed by the zoochoric agent, these inhibitors are removed either through digestion by saliva or passage through their alimentary canal and thus improve germination potential when finally dispersed to distant locations (Kiepiel and Johnson, 2019;Kissmann and Habermann, 2013;Pegman et al, 2017;Yagihashi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Clivia is also the study subject of frequent fungal diseases in tropical plants Liu et al, 2020). e toxicity of C. miniata fruits and seeds has been studied (Kiepiel & Johnson, 2019), as well as the genes involved in the formation of Clivia leaves (Qin-Mei et al, 2018;Wang et al, 2016). Changes in the pollinator community of Scadoxus cinnabarinus along its altitude belt on Mount Cameroon have been studied by a group of Czech and African scientists (Mertens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%